Sustainable Livelihood of Households in Tourism Destination: Evidence From in the Wulingyuan World Heritage Site - Zhang Qian; Liu Siyi; Liu Jing; Julie Jie Wen (Randwick International of Social Science Journal, 2022)
In the process of resource protection and development of World Heritage Sites, the sustainability of the livelihoods of heritage site residents is one of its important tasks. Taking Wulingyuan, a world heritage tourism site, as an example to construct the livelihood evaluation index system of households, and use the participatory farmer survey method to conduct household surveys on households. Based on livelihood strategies, households are divided into different types of livelihood, their livelihood capital is assessed, and their livelihood obstacle factors are identified. The research results show that: Under the influence of rural tourism development, households' livelihood capital has been improved as a whole. There are differences in the level of livelihood capital of different types of households. From high to low, they are: tourism-dominant type, working-dominant type and agricultural--dominant type. The World Heritage Site households' Sustainable Livelihood Obstacle Index is ranked from high to low as social capital, human capital, financial capital, natural capital, and physical capital; the top three indicators are: online social media, social network support, family farmland area. Different types of households have different obstacles, social capital is the biggest obstacle in common among the three types of households, and the primary obstacle is online social media.